Setting the Table for Julia Child Gourmet Dining in America, 1934-1961 - Strauss, David (Johns Hopkins University Press, 2011)
Before Julia Child's warbling voice and towering figure burst into America's homes, a gourmet food movement was already sweeping the nation. Setting the Table for Julia Child considers how the tastes and techniques cultivated at dining clubs and in the pages of Gourmet magazine helped prepare many affluent Americans for Child's lessons in French cooking. David Strauss argues that Americans' appetite for haute cuisine had been growing ever since the repeal of Prohibition. Dazzled by visions of the good life presented in luxury lifestyle magazines and by the practices of the upper class, who adopted European taste and fashion, upper-middle-class Americans increasingly populated the gourmet movement. In the process, they came to appreciate the cuisine created by France's greatest chef, Auguste Escoffier. Strauss's impressive archival research illuminates themes-gender, class, consumerism, and national identity-that influenced the course of gourmet dining in America. He also points out how the work of painters and fine printers-reproduced here-called attention to the aesthetic of dining, a vision that heightened one's anticipation of a gratifying experience. In the midst of this burgeoning gourmet food movement Child found her niche. The movement may have introduced affluent Americans to the pleasure of French cuisine years before Julia Child, but it was Julia's lessons that expanded the audience for gourmet dining and turned lovers of French cuisine into cooks.